2017
DOI: 10.3892/etm.2017.5500
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of human ovarian cancer cells is enhanced by pseudolaric acid B due to the inhibition of the Ras/Raf/ERK signaling pathway

Abstract: Ovarian cancer has the highest mortality rate among gynecological cancers; the most effective therapy for this cancer is a combination of radiation treatment and chemotherapy. However, radiation resistance is the leading factor associated with treatment failure. The present study aimed to investigate pseudolaric acid B (PAB) as a potential radiosensitizer for the treatment of ovarian cancer. The present study performed MTT and clonogenic assays, and demonstrated that PAB could induce a radiosensitizing effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…We investigated significantly enriched KEGG pathways and the key target genes associated with these pathways. Our findings were in line with a range of previous studies, with respect to choline metabolism [27], the Ras-Raf-ERK signaling pathway [28], the estrogen receptor pathway [29], MAPK1 [30], PRKCB [31], PIK3CA [31], NRAS [32], PIK3R3 [33] and SOS1 [34]. These pathways have all been demonstrated to play vital roles in the aggressiveness, growth, and metastasis of OVC.…”
Section: Discussionsupporting
confidence: 92%
“…We investigated significantly enriched KEGG pathways and the key target genes associated with these pathways. Our findings were in line with a range of previous studies, with respect to choline metabolism [27], the Ras-Raf-ERK signaling pathway [28], the estrogen receptor pathway [29], MAPK1 [30], PRKCB [31], PIK3CA [31], NRAS [32], PIK3R3 [33] and SOS1 [34]. These pathways have all been demonstrated to play vital roles in the aggressiveness, growth, and metastasis of OVC.…”
Section: Discussionsupporting
confidence: 92%
“…OC is a gynecological tumor with a high mortality rate, whose first-line therapy is combination of radiation treatment and chemotherapy [22]. However, drug resistance is one of the reasons that can lead to therapy failure.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular signal-regulated kinase (ERK) signaling pathway regulates cell proliferation, differentiation and survival, and mediates and amplifies signals during tumor invasion and metastasis (36). Previous studies have demonstrated that the extracellular signal-regulated kinase (ERK) signaling pathway is associated with tumor radiation resistance (37,38). In addition, previous studies have indicated that TRIM36 serves an inhibitory effect on the ERK signaling pathway in prostate cancer (39).…”
Section: Discussionmentioning
confidence: 99%